A revised evolutionary history of armadillos (Dasypus) in North America based on ancient mitochondrial DNA. (4th August 2014) - Shapiro, Beth; Graham, Russell W.; Letts, Brandon
<x xml:space="preserve">Abstract</x> The large, beautiful armadillo, Dasypus bellus, first appeared in North America about 2.5 million years ago, and was extinct across its southeastern US range by 11 thousand years ago (ka). Within the last 150 years, the much smaller nine‐banded armadillo, D. novemcinctus, has expanded rapidly out of Mexico and colonized much of the former range of the beautiful armadillo. The high degree of morphological similarity between these two species has led to speculation that they might be a single, highly adaptable species with phenotypical responses and geographical range fluctuations resulting from environmental changes. If this is correct, then the biology and tolerance limits for D. novemcinctus could be directly applied to the Pleistocene species, D. bellus. To investigate this, we isolated ancient mitochondrial DNA from late Pleistocene‐age specimens of Dasypus from Missouri and Florida. We identified two genetically distinct mitochondrial lineages, which most likely correspond to D. bellus (Missouri) and D. novemcinctus (Florida). Surprisingly, both lineages were isolated from large specimens that were identified previously as D. bellus. Our results suggest that D. novemcinctus, which is currently classified as an invasive species, was already present in central Florida around 10 ka, significantly earlier than previously believed.